Rapid evolution of larval life history, adult immune function and flight muscles in a poleward‐moving damselfly. (7th December 2013) - Therry, L.; Nilsson‐Örtman, V.; Bonte, D.; Stoks, R.
Abstract Although a growing number of studies have documented the evolution of adult dispersal‐related traits at the range edge of poleward‐expanding species, we know little about evolutionary changes in immune function or traits expressed by nondispersing larvae. We investigated differentiation in larval (growth and development) and adult traits (immune function and flight‐related traits) between replicated core and edge populations of the poleward‐moving damselfly Coenagrion scitulum. These traits were measured on individuals reared in a common garden experiment at two different food levels, as allocation trade‐offs may be easier to detect under energy shortage. Edge individuals had a faster larval life history (growth and development rates), a higher adult immune function and a nearly significant higher relative flight muscle mass. Most of the differentiation between core and edge populations remained and edge populations had a higher relative flight muscle mass when corrected for latitude‐specific thermal regimes, and hence could likely be attributed to the range expansion process per se. We here for the first time document a higher immune function in individuals at the expansion front of a poleward‐expanding species and documented the rarely investigated evolution of faster life histories during range expansion. The rapid multivariate evolution in these ecological relevant traits between edge and core populations is expected to translate into changed ecological interactions and therefore has the potential to generate novel eco‐evolutionary dynamics at the expansion front.